Isolation of HMW DNA from sunflower (Helianthus annuus L.) for BAC cloning - Özdemir, N; Horn, R; Friedt, W (INT SOC PLANT MOLECULAR BIOLOGY, 2002)
The cultivated sunflower (Helianthus annuus L.) is one of the most important oil crops in the world. The importance of sunflower oil in human nutrition and in the chemical industry makes the sunflower a major research interest. An essential element for genomic libraries is the preparation of high molecular weight (HMW) DNA. We developed 2 methods for isolating HMW sunflower DNA. We prepared the DNA from nuclei and from protoplasts isolated from mesophyll tissue with the enzymes cellulase RS and pectolyase Y23. The HMW DNA was digested with restriction endonucleases. The ethidium bromide-stained gel suggested the DNA to be completely digested. These results were confirmed by Southern analysis using a radiolabeled RFLP marker. Both methods made it possible to generate sufficient quantities of megabase-size sunflower DNA suitable for bacterial artificial chromosome (BAC) cloning.
Keywords: BAC cloning; Helianthus annuus; HMW DNA; PFGE; sunflower; ARTIFICIAL CHROMOSOME LIBRARY; MEGABASE-SIZE DNA; ESCHERICHIA-COLI; CONSTRUCTION; YEAST; RESISTANCE; MOLECULES; BACTERIAL; GENE; SEPARATION; Biochemistry & Molecular Biology; Plant Sciences